New insights into the effect of wind assistance on sprinting performance - Ward-Smith, A. J. (Journal of Sports Sciences, 1999)
Here, a new mathematical model of sprinting is proposed. The prediction method rests on the construction of an energy balance incorporating a mathematical representation of each of the major terms in the balance. The term expressing the degradation of mechanical energy into thermal energy is formulated to express a dependence on wind speed. The dependence of the drag term on the change in mean body angle relative to the horizontal is taken into account. Whereas the effect of modifying the degradation term is shown to be significant, changes in body lean angle are shown to have little effect. Comparisons of the present predictions with a previous statistical analysis of 100-m track data show good agreement. Sensitivity analyses show which variables have the greatest influence on sprinting performance.